ECONOMIC JUSTIFICATION OF APPLYING INFORMATION TECHNOLOGIES TO THE CREATION OF SMART CITI - Radojcic, Vesna; Sandro Cvetkovic, Aleksandar (The European Journal of Applied Economics, 2022)
Modern technologies, in addition to making people's lives easier, faster and better, enable the combination of different technologies to develop solutions to various problems. Global warming is one of the biggest and most dangerous problems facing planet earth. If global warming were presented as a coin, then air pollution and climate change would be two sides of the same coin. Climate change is primarily a problem that has arisen due to the large amount of carbon dioxide (CO2) in the atmosphere. Carbon overload occurs mainly due to the combustion of fossil fuels such as coal, oil and gas, or the cutting and burning of forests. There are other harmful gases but CO2 stands out because it poses the greatest risk of irreversible change if it continues to accumulate in the atmosphere. This paper presents a number of different solutions by combining modern technologies for the problem of CO2 emissions globally, where Bosnia and Herzegovina is particularly singled out as one of the countries with the most polluted air in Europe and with the highest mortality rate associated with air pollution. Smart cities use digital technologies, aim to improve the quality of human life and to enable the protection of the environment. The concept of a smart city is described as a set of modern technologies, examples of leading smart cities in the world are given, as well as the advantages of implementing such a solution
Keywords: smart city, air pollution, climate change, reducing carbon dioxide emissions, global warming, CO2 emissions